The Customer Perspective on Food Delivery Applications: Insights from Saudi Arabia - Alotaibi, Asma; Alofan, Fahad (Archives of Business Research, 2024)
In today’s technology-driven era, online platforms and applications have revolutionized various services, including food delivery and offering unparalleled convenience and efficiency. This surge in popularity of digital solutions is driven by consumers’ growing technological dependency and their quest for seamless experiences. Consequently, more restaurants outsource delivery services to meet evolving consumer preferences. This study provides business operators with valuable insights into consumer preferences and behaviors regarding online food delivery applications. Specifically, it identifies the determinants influencing the adoption of such apps and explores the most popular apps among the Saudi subpopulation. Additionally, this study investigated the factors associated with the actual usage of online food delivery services. An analysis of the collected data revealed critical factors shaping consumer choices in food delivery services, notably the impact of social media reputation and advertisements. The proximity of restaurants has emerged as a significant determinant, profoundly influencing customer satisfaction and app preferences. Interestingly, while cost did not significantly drive consumers towards online food delivery services, the Jahez app stood out as the preferred choice because of its exemplary customer service. The findings of this study offer valuable insights for informed strategic decision-making within the food delivery ecosystem. Moreover, recommendations for future research are provided to foster a deeper understanding of and innovation in the online food delivery domain.